Students’ Difficulties In Multivariable Calculus Through Mathematical Thinking Approach - Kashefi, Hamidreza (Fakulti Pendidikan, 2011)
The purpose of this study is to identify students’ difficulties in Multivariable Calculus through mathematical thinking approach at Universiti Teknologi Malaysia (UTM). The data collection for this study was collected from a Multivariable Calculus class in Faculty of Electrical Engineering during semester I 2009-2010. Data collection was carried out through written assessments and structured questionnaires. The data analysis reveals that students’ common difficulties are: students’ met-before (previous experience), selecting appropriate representation of the three worlds of mathematical thinking, the transition from one world to another world of mathematical thinking, lack of understanding two different symbolic for a concept, and poor prior knowledge or lack of it. The findings show that the sketching in 3-dimensions is the greatest difficulty for majority of students in this method. Keywords: Mathematical Thinking; Basic Calculus; Multivariable Calculus; Students’ difficulties.